The effect of positioning strategy on firms' performance moderated by product market competition - Tessarolo, Guilherme Lecco (2020)
This research aims to investigate the effect of positioning strategies, adopted in a pure or hybrid way, on firms performance. In addition, it verifies the moderating effect of product market competition in this relationship, in order to analyse under whi